Semiotika: Sebuah Pendekatan dalam Studi Agama - Khotimah, Khusnul (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
Semiotic is a science about sign in form word, picture, sound and literary work. Semiotic often used asapproach to analyze text, in order to formulate structure and possible meaning, and often used as approach in socialculture matter, literary works and religious texts. In religious texts, we can see Arkoun’s reading on surah al-Fatihah, when basicassumes offered by Arkoun based on al-Qur’an that according to him have open characteristic by using syntax andsemantic analysis. Netton also using semiotic approach that focused to reveal meaning behind Suhrawardi works.